Targeting the NLRP3-ROS Axis: Disrupting the Oxidative-Inflammatory Vicious Cycle in Intracerebral Hemorrhage - Cao L; Pi W; Zhang Y; Zheng C; Yong VW; Xue M (Journal of Inflammation Research)
Liang Cao,1,2 Wenjun Pi,3 Yi Zhang,4 Chunfu Zheng,5 Voon Wee Yong,6 Mengzhou Xue1,2 1Department of Cerebrovascular Diseases, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 2Henan International Joint Laboratory of Intracerebral Hemorrhage and Brain Injury, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 3Department of Traumatic Orthopedics, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 4Office of Research, Shunyi Maternal and Children’s Hospital of Beijing Children’s Hospital, Beijing, People’s Republic of China; 5Department of Microbiology, Immunology and Infectious Diseases, University of Calgary, Calgary, Alberta, Canada; 6Hotchkiss Brain Institute and Department of Clinical Neurosciences, University of Calgary, Calgary, Alberta, CanadaCorrespondence: Voon Wee Yong; Mengzhou Xue, Email vyong@ucalgary.ca; xuemengzhou@zzu.edu.cnAbstract: Intracerebral hemorrhage (ICH) is a highly fatal disease that currently lacks effective treatment options. However, secondary brain injury has become a key focus in translational research, with oxidative stress (OS) identified as a central factor in ICH pathophysiology. Following ICH, hematoma components and inflammatory factors overwhelm the antioxidant defense system, triggering OS. Concurrently, neuroinflammation arises, driven by activated microglia that adopt a pro-inflammatory phenotype and release cytokines and chemokines. While neuroinflammation may support repair, it can also cause harmful secondary damage. Recent evidence indicates that NLRP3 is an important inflammasome considered a key player in OS and neuroinflammation. OS can activate the NLRP3 inflammasome by producing reactive oxygen species (ROS), further exacerbating the inflammatory response. Additionally, NLRP3 also plays an important role in regulating neuroinflammation. The activation of the NLRP3 inflammasome promotes the release of pro-inflammatory cytokines, further intensifying the neuroinflammatory response. The activation of NLRP3 is closely related to the polarization of microglia, potentially driving microglia to polarize towards the M1 type (pro-inflammatory), thereby exacerbating neuroinflammation. Therefore, we hypothesize that NLRP3 plays a critical regulatory role in OS and neuroinflammation following ICH. This review summarizes the regulatory role of the NLRP3 inflammasome in the interplay between OS and neuroinflammation, as well as its potential therapeutic targets related to ICH.Keywords: intracerebral hemorrhage, NLRP3 inflammasome, oxidative stress, neuroinflammation, brain injury